O-029 Brain tissue iron quantification at the periphery of the hematoma by MRI in patients with intracerebral hemorrhage: translational evidence in first 10 patients - Chaudhary, N; Pandey, A; Griauzde, J; Gemmete, J; Keep, R; Xi, G (Journal of neurointerventional surgery, 2019)
ObjectiveIntracerebral hemorrhage (ICH) has devastating consequences in the human population. No specific outcome modifying treatment or objective risk stratifying measure currently exists in ICH patients. The goal of our study is to validate an MRI based algorithm to reliably quantify the iron levels in the periphery of the hematoma.MethodsInstitutional IRB was obtained for the study. We secured NIH funding to undertake the study in September 2018. We recruited 10 patients based on inclusion and exclusion criteria established for the study. The study protocol was to obtain MRI at day 3, 14 and 30 following ICH. The MRI scans were performed without contrast. The sequences performed were T1, T2 and PADRE plus a multi-echo susceptibility weighted sequence. Relaxivity (1/T2* - R2*) maps were then created utilizing the multi-echo sequence in Matlab. Two consecutive volumes of interest (VOI) 1 & 2 rings were then manually drawn on the maps around the periphery of the hematoma, on all the axial slices demonstrating the hematoma, on all available date points in each individual patient. Identical contralateral brain VOI (Normal Control - NC) was also drawn at each corresponding MRI axial image slice. The average measurement values were then tabulated at pre-specified time points over a period of one month following the ICH. The R2* value was then extrapolated to an iron concentration (IC) measured from an iron phantom MRI with identical sequences.Results10 eligible patients with ICH and two controls were recruited to the study. The Mean R2* value Day 3: VOI 1; 53.59 (SD: 6.01) - IC 0.16 SD 0.02, VOI 2: 28.35 (SD: 5.17) - IC 0.08 SD 0.02, NC: 19.47 (SD: 2.85) - IC 0.05 SD 0.01. Day 14: VOI 1; 47.97 (SD: 5.43) - IC 0.14 SD 0.02, VOI 2: 27.19 (SD: 2.19) - IC 0.08 SD 0.01, NC: 18.94 (SD: 1.62) - IC 0.05 SD 0.01. Day 30: VOI 1; 49.14 (SD: 6.44) - IC 0.15 SD 0.02, VOI 2: 30.10 (SD: 3.41) - IC 0.09 SD 0.01, NC: 19.93 (SD: 2.82) - IC 0.05 SD 0.01.ConclusionOur study, the first translational study of its kind, shows relatively reliable iron concentration measurements by MRI at the periphery of the hematoma over a period of 1 month following the ICH, showing good correlation with previous animal study data over a similar duration. Larger study is needed with extended 180 day follow up to further validate the measurement algorithm with a view to potentially becoming an MRI based risk stratification strategy in ICH patients. In addition, the algorithm may be utilized for monitoring iron chelate therapy in ICH.Disclosures N. Chaudhary: None. A. Pandey: None. J. Griauzde: None. J. Gemmete: None. R. Keep: None. G. Xi: None.